2020
DOI: 10.1002/adom.201900982
|View full text |Cite
|
Sign up to set email alerts
|

Narrow‐Band Thermal Emitter with Titanium Nitride Thin Film Demonstrating High Temperature Stability

Abstract: generation, [4][5][6] radiative cooling, [7] and thermophotovoltaics (TPVs). [8] When selective thermal emitters are intended to emit in shorter mid IR range (e.g., an emitter for TPV system), the emitter has to be heated above one thousand kelvin. [9] Refractory metals such as molybdenum (Mo) [10] and tungsten (W) [11] are required in such cases. However, searching for alternative plasmonic materials is essential for reducing the material cost as well as for material research interest.Transition metal nitride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…On one hand, an ultrahigh vacuum condition is generally required during the growth of TiN thin films . On the other hand, devices with TiN operated at high-temperature usually need to be carefully vacuumed, , sealed in inert gases, or covered by an optically transparent protective layer . Previous studies have pointed out that the oxidation level of TiN is mainly controlled by temperature, oxygen partial pressure, and time. Although several studies have indicated the impact of crystallographic orientation on the chemical reactivity of materials (metals, transition metal oxides, and organic materials), its role in the oxidation of TiN thin films and resultant plasmonic performance is still unclear yet due to the lack of high-quality epitaxial TiN films with various controllable crystallographic orientations on the same substrates.…”
mentioning
confidence: 99%
“…On one hand, an ultrahigh vacuum condition is generally required during the growth of TiN thin films . On the other hand, devices with TiN operated at high-temperature usually need to be carefully vacuumed, , sealed in inert gases, or covered by an optically transparent protective layer . Previous studies have pointed out that the oxidation level of TiN is mainly controlled by temperature, oxygen partial pressure, and time. Although several studies have indicated the impact of crystallographic orientation on the chemical reactivity of materials (metals, transition metal oxides, and organic materials), its role in the oxidation of TiN thin films and resultant plasmonic performance is still unclear yet due to the lack of high-quality epitaxial TiN films with various controllable crystallographic orientations on the same substrates.…”
mentioning
confidence: 99%
“…In this work, the ZnO film is only 1/10 the thickness of the wavelength, and only half the thickness of the traditional microcavity structure. [43] Because the TPP mode has the ability to confine the electric field in the surface between DBR and metal, light, and matter can interact in such a small space to form polaritons. Polaritons can condensate at the ground state through stimulated scattering, forming polariton emissions.…”
Section: Discussionmentioning
confidence: 99%
“…A few designs utilizing metal nitrides as high‐temperature solar‐thermal converter have been demonstrated. [ 141–143 ]…”
Section: Plasmonic Nanostructures Tailored For Specific Applicationsmentioning
confidence: 99%